(3GdSdSdI GdbGOQjIs - (3MSjf Hf MSjf Hf YHO Gddg Hf CHj HcQ GdTQja GdEOcGhj , GdTQja,J (B1237 (3g` s
(3ChdgG (B:s
(3eHJhQ , hChd GdehLhO efgG (B: (3hhGdOi hTjNi hbO hbi CHh YeO GdTjN Yaja GdOjfe YHO Gddg Hf CHj HcQ Hf GdTjN YHO GdQMef GdMSjfi s
(3BNQgG (B:s
(3eHJhQ , hBNQgG eG ajgG (B: (3hfhQ ShGO bdHi hEfSGf Yjf HUjQJi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B5s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B295 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B231 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs